HISTORICAL CONTEXT OF YURI LYPA NOVEL “RUBAN”: CRITICAL ANALYSIS OF THE LITERARY SOURCE OF THE LIBERATION ERA 1917–1922 (Південний архів (історичні науки), 2023)
Purpose. The article is devoted to Yuriy Lypa novels, which refer to the events of Ukrainian revolution of 1917–1921. They are and they can be subject of literary analysis, of reconstruction of historical events, of the analysis of revolution period results for realization of its historical lessons. The aim of article is archive interest of readers to these composition, new attentive reading of them in terms of rethinking of revolutionary events in Ukraine in 1917–1921. Y. Lypa drew a little-known episode from the history of atamanship during the period of Ukranian revolution was focused on the basis of new archive sources. The purpose of the article is to draw readers’ attention to these works of Y. Lypa, as a variant of alternative history, their new and careful reading in the context of reinterpretation of the events of the liberation struggles of 1917–1922. Methods. The research is based on the synergy of interdisciplinary methodical optics: a critical method of analyzing literary and historical sources. The methods of hermeneutic text analysis are used to analyze the author’s narrative. To compare the historical figures of Ukrainian chieftains mentioned on the pages of the novel, we use the biographical and comparative methods. Historical-typological and comparative analysis is used during the analysis of the uprising and atamanship. An interdisciplinary will be used to analyze literary sources: source deconstruction and techniques of historical hermeneutics. The results. Literary and historical sources related to the personalities of Ukrainian chieftains mentioned in Y. Lypa’s novella “Ruban” are analyzed. The historical reliability of the events mentioned by the author has been clarified. Attention is focused on the peculiarities of worldview, activity, motivation of decisions made by chieftains of the period of liberation struggles. A distinction is made between credible historical information and the author’s fiction. The place and significance of these personalities in the history of the Ukrainian anarchist movement during the period of the liberation struggles of 1917–1921 has been clarified. Conclusion’s. Y. Lypa novella “Ruban” is an example of an artistic interpretation of the processes of the Ukrainian revolution of 1917–1921. First of all, such phenomena as the uprising and atamanship, the phenomenon of multiple sovereignty: the creation of peasant republics in Central and Southern Ukraine. It has been established that the image of the rebel leader, Ataman Ruban, is collective. He combines the features, manner of behavior, tactics, worldview of several Ukrainian chieftains. In the article, the author draws attention to these personalities. The author, using archival sources and modern research on the history of the Ukrainian uprising and chiefdom, refutes the hypothesis that chieftain Ruban had his specific prototype. These phenomena, artistically depicted and analyzed by Y. Lypa, can become an interesting and promising research platform for scientific studies on historical regionalism, primarily of Central and Southern Ukraine.
Keywords: Ukrainian revolution of 1917–1921, ukrainian rebels, Yuriy Lypa, atamanship, literature sourse, multiple sovereignty